Implementasi Metode Analytical Hierarchy Process untuk Keputusan Pemberian Ijin Operasional Sekolah Tingkat SMA/SMK di Kabupaten Sumba Barat - Herlina Yasinta Duki; Andreas Ariyanto Rangga; Lidia Lali Momo (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
In order for students to actively develop their potential for religious spiritual strength, self-control, personality, intelligence, morality, life sciences, general knowledge, and the skills they need for society based on the law, education is a planned basic effort to create a learning atmosphere and learning process. Invite. Although it can also be autodidactic, education frequently takes place with the assistance of other people as well as biological parents. Preschool, elementary school, middle school, high school, and finally college, university, or apprenticeship are the typical phases of education. Another important factor in a region's development is education. Therefore, a decision support system that can make suggestions for choosing state institutions and study programs is required for West Sumba Regency SMA/Vocational Schools. The Analytical Hierarchy Process (AHP) approach is used to weight the value of each criterion, and the Simple Additive Weighting (SAW) method is used to calculate the weighted total or to order the alternatives from best. The weights of each alternative—a state university or study program—along with all of its features are added up to determine recommendations for selecting one. The chosen option will be indicated by a higher value. This system generates a report on the outcomes of management decisions, which includes the management's selections based on all options arranged from greatest to smallest SAW value. MySQL and Microsoft Visual Studio 2008 were used to develop the decision support system suggestions for choosing state colleges and study programs for the database.